Unraveling Complexity: Deep Vein Thrombosis as an Intriguing Complication of Scrub Typhus Infection - Anurag Bhattacharjee; K Elancheralathan; Ashok Kumar; Ruru Ray; Rajkumar Thangavel; Sharath Rajkumar (Indian Journal of Vascular and Endovascular Surgery)
Scrub typhus, an emerging infectious menace in India, is caused by Orientia tsutsugamushi, transmitted through larval trombiculid mites. Despite its typical presentation as undifferentiated febrile illness, scrub typhus can manifest severe complications, including the rare occurrence of deep vein thrombosis (DVT). We present a noteworthy case of DVT in a 35-year-old female with scrub typhus, delving into the intricate interplay between rickettsial infection and vascular pathology, and exploring contemporary therapeutic strategies.